Radio behavior of four southern non-thermal O-type stars - Benaglia, Paula (2007)
We have conducted high resolution continuum observations at 1.4 and 2.4 GHz  with the Australia Telescope Compact Array, towards the four southern Of stars: CD-47 4551, HD 93129A, HD 124314, and HD 150136. All stars have been detected at the two frequencies. HD 93129A - the only O2 I star catalogued so far, and in a double system -, has also been observed at 17.8 and 24.5 GHz. Its radio spectrum, complemented with previous observations at higher frequencies, is analyzed here. The interpretation yields the estimate of its mass loss rate, and a non-thermal spectral index of radiation coming from a putative colliding wind region. The synchrotron and corresponding inverse Compton luminosities are derived.